Pengaruh Profitabilitas, Ukuran Perusahaan, Leverage, dan Struktur Kepemilikan Terhadap Nilai Perusahaan - Amalia Nony Laila Parytri; Eni Wuryani (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
The purpose of this research is to examine profitability, company size, leverage, and ownership structure on company value. This research uses secondary data from annual reports of industrial sector companies listed on the IDX during the 2019-2022 period. The population in this study was 56 companies using purposive sampling techniques, resulting in 14 companies so that the total sample for 4 years was 56 samples. Data processing uses SPSS version 26 with multiple linear analysis methods. Based on the results of the analysis carried out, it is known that profitability and leverage have no effect on company value, while company size, managerial ownership and institutional ownership have an effect on company value.